Association of On-Admission Anemia With 1-Year Mortality in Patients Hospitalized With Acute Heart Failure: Results From the HERO Study - Li, Junlei; Jiang, Chao; Lai, Yiwei; Li, Li; Zhao, Xiaoyan; Wang, Xiaofang; Li, Ling; Du, Xin; Ma, Changsheng; Dong, Jianzeng (Frontiers in Cardiovascular Medicine, 2022)
Background: Anemia is common in patients with chronic heart failure (HF) and is associated with adverse outcomes. However, data regarding the prognostic value of on-admission anemia on mortality in patients hospitalized with acute HF were relatively limited and conflicting. This study aimed to investigate the association of on-admission anemia with 1-year mortality and evaluate whether anemia is an independent predictor of mortality in patients hospitalized with acute HF. Methods: The present analysis included 4,244 patients hospitalized with acute HF from the HERO (Heart Failure Registry of Patient Outcomes) study. On-admission anemia was defined using the World Health Organization (WHO) criteria (hemoglobin<120g/L in women and <130g/L in men). Cox proportional hazards models were used to assess the association of anemia with 1-year all-cause and cardiovascular mortality. Results: Of 4244 patients, 2206(52.0%) patients had no anemia, 1106(26.1%) patients had mild anemia (men 110≤ hemoglobin<130g/L; women 110≤ hemoglobin<120g/L), and 932 (22.0%) patients had moderate-to-severe anemia (hemoglobin<110g/L). After a median follow-up of 12.4 months (interquartile range: 11.9, 12.6), 867(20.4%) patients died. Among the 742(85.6%) deaths with confirmed causes, 664(89.5%) were due to cardiovascular diseases. The mortality rates in patients with no anemia, mild anemia, and moderate-to-severe anemia were 16.6%, 20.4%, and 29.4%, respectively(p<0.001). The association of anemia with increased all-cause mortality was significant in the unadjusted model (hazard ratio [HR]: 1.54, 95% confidential interval [CI]: 1.35-1.77, p<0.001), and remained statistically significant after adjustment for most potential confounders (HR: 1.20, 95%CI: 1.03-1.40, p=0.020), but no longer significant after additional adjustment for natriuretic peptides (HR: 1.02, 95%CI: 0.86-1.21, p=0.843). When considering the degree of anemia, moderate-to-severe anemia was an independent predictor of all-cause mortality after full adjustment (HR:1.26, 95%CI: 1.03-1.54, p=0.028), whereas mild anemia was not (HR: 0.84, 95%CI: 0.69-1.04, p=0.104). A similar relationship was also found between anemia and cardiovascular mortality. Conclusions: On-admission anemia, defined by the WHO criteria, is not an independent predictor of mortality in patients hospitalized with acute HF. Moderate-to-severe anemia in patients with acute HF is independently associated with increased mortality.